Effect of Autonomous Vehicles on Car Rental Services in Sri Lanka - I.E. Madiwilage; O.G. Amaraweera; N.G.U.I. Disanayake; M.L. Sandeepani; D. I. De Silva; S.M.D.T.H. Dias (International Journal of Engineering and Management Research, 2022)
This paper will introduce a special kind of logistics management problem which exists in the car rental industry. In order to get a high degree of customer satisfaction and optimize vehicle fleet utilization, logistics managers in the car rental business have predicted few technologies: namely Autonomous driving and on demanding rentals. These ideas that will be seen in action in the near future approximately 10 years from now on. Optimizing resource deployment and reducing the logistics cost are the targets of logistics management in enterprise. This sort of research is prospective and useful for future development of the car rental industry.